Special Allocation Fund and Poverty Rate in Indonesia - Danesta Febianto Nugroho; Bayu Rhamadani Wicaksono; Muhammad R. Reynaldi (Economics and Finance in Indonesia, 2021)
The Special Allocation Fund is distributed to specific areas to aid them in funding special regional activities that follow national interests. Giving regional government’s broad autonomy is meant to hasten the realization of social welfare, as seen by reducing poverty. This study aims to examine the influence of the Special Allocation Fund for education, health, and infrastructure on the poverty rate in Indonesia, using the Poverty Gap Index (P1) as a proxy for the poverty rate. The study employed annual data from 33 Indonesian provinces from 2015 to 2018 and panel data regression analysis utilizing the Fixed Effects Model (FEM). The study discovered that the Special Allocation Fund for Education and Health has a negative and significant impact on poverty, but the Special Allocation Fund for Infrastructure has a positive but not significant impact on poverty. The central and regional governments must work together to guarantee that the Special Allocation Fund is distributed effectively to sectors directly relevant to poverty reduction efforts.